Epidemiology of Fire Blight in Fruit Crops in Kazakhstan - Umiraliyeva, Zhansaya Ziyathanovna; Kopzhassarov, Bakyt Kenzhekozhaevich; Jaimurzina, Aliya Abdrahimovna; Niyazbekov, Zhan Borisovich; Issenova, Gulmira Zhanybekovna; Tursunova, Alnura Kairatovna; Berganayeva, Gulzat Ergaziyevna (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
A survey on 13 regions of Kazakhstan was carried out to identify foci of fire blight, the extent of its spread, the range of affected crops, and the identification of infection reserves. The disease was mainly concentrated in the main fruit growing zone.at the south and southeast of Kazakhstan. Symptoms of fire blight were characteristic of two bacterial diseases: namely, necrosis, by Pseudomonas syringae Van. Hall. and fire blight by Erwinia amylovora (Burrill) Winslow et al. The authors performed bacteriological analyses to isolate and identify the causative agent of fire blight from various fruit and wild cultures of the Rosaceae family, using classical bacteriological and molecular genetic methods. Two types of bacteria were isolated from the samples affected by the disease, namely E. amylovora, the causative agent of fire blight, and P. syringae, the causative agent of bacterial necrosis. The results of the studies on the identification of bacterial species E. amylovora and P. syringae were confirmed by Swiss scientists from the Agroscope research center based on an immuno-chromatographic test and by Russian scientists at the All-Russian Research Institute of Plant Quarantine using enzyme-linked immunosorbent assay, FLASH polymerase chain reaction, and polymerase chain reaction in real-time.